The Relevance Of The Principle Of Maqashid Al-Syari'ah In The Procedure For Settlement Of Sharia Pawn Disputes In Indonesia - M. Ihsan (International Journal of Economics, Business and Innovation Research, 2025)
The sharia pawn ( rahn ) institution continues to show a positive growth trend in Indonesia, increasing access to financing while also increasing the potential for disputes between the rahin (pawn giver) and the murtahin (pawn recipient). This research aims to analyze the forms of sharia pawn disputes in Indonesia, examine the rules and practices of dispute resolution efforts, and analyze the relevance of these resolution efforts from the perspective of Maqashid Al-Syari'ah . The research method used is qualitative with a case study approach at the Sharia Business Unit of PT. Pegadaian and the National Sharia Arbitration Board ( Basyarnas ) MUI. The results identify four main forms of dispute: differences in contract interpretation, issues of damage/loss of the pawned object, differences in the appraised value of the pawned object, and customer rejection of the auction. Dispute resolution is carried out hierarchically through deliberation to reach consensus ( al-Sulh ) , Basyarnas Arbitration ( Tahkim ) , and the Religious Court ( al- Qadha ) . When reviewed from the perspective of Maqashid Al-Syari'ah , dispute resolution must be based on the principle of good faith , which substantially aims to realize Hifdzu al-Maal (preservation of property) and produce maslahah (benefit) for all parties.